PRAGMATIC TRANSFER IN REQUEST REALIZATIONS - Indawan Syahri; A. Effendi Kadarisman (TEFLIN, 2007)
This study investigates the pragmatic transfer in English request realizations made by EFL learners, i.e. the proficient learners. The subjects were students of an English Study Program who obtained TOEFL-like scores of at least 450. The data were collected by means of DCT-questionnaires and Role-plays. The results show that the subjects realize requests in the form of external modifications more frequently. Most of them embed their requests with supportive moves dominantly. They enfold the acts with the moves before, after or in both positions. Of the three positions, they mostly insert the moves initial position, i.e., through inductive patterns. This is due to pragmatic transfer.